The Level of Frequency of Tourist Visits In Paloh Naga Agrotourism - Simatupang, Donny Ivan Samuel; Pakpahan, Helena Tatcher; Perangin-Angin, Rizky Ananda (Publikasi Indonesia, 2023)
The level of tourist visits in Paloh Naga agrotourism two sub-variables can affect the level of tourist visits, namely: Beauty of Tourist Objects (KW1), Originality of Tourist Objects (KW2). This study aims to determine the level of visits in frequency in Paloh Naga agrotourism. The research determination method was carried out with a Purposive (Intentional) namely Agrotourism Paloh Naga 1, Denai Lama Village, Labu Beach District. Deli Serdang Regency, North Sumatra Province. The results of this study show that 2 sub-variables can affect the level of visitation, namely: the beauty of objects has a low category of 94%, medium as much as 6%, and high as much as 0%. The originality of objects has a low category of 89%, medium as much as 11%, and high as much as 0%.